Multi-criteria analysis on spatial data of the landscape - Jarosz, Paweł; Łabędź, Piotr; Ozimek, Paweł (Computer Assisted Methods in Engineering and Science, 2019)
The method presented in this paper allows the visualization of spatial relations that could not be obtained using existing methods. Depending on the component maps that represent the analysis criteria, it is possible to indicate certain ways to develop good or bad areas. These maps may contain visibility data as well as other types of spatial impact. Thanks to this, spatial decision criteria can be broad and multibranch.